FUNDAMENTALISME DAN UPAYA DERADIKALISASI PEMAHAMAN AL-QURâ€™AN DAN HADIS - Muhamad Harfin Zuhdi (Religia, 2010)
â€œFundamentalism is identical with violenceâ€, this stereotype is conserved by the West for centuries. Islamic fundamentalism is a cause of many violence, suicidal bomb, murder, war, and terrorism that is strengthened by holy war (jihad) doctrine. One of these movement foundations is verses of the Quran and Hadith about war. This paper is not meant to correct or criticize those Quranic verses or Hadith, but it is meant to criticize the interpretation those Quranic verses or Hadith. In this context, de-radicalization of that interpretation becomes very significant because it is expected that it can give solution for the strained situation happening in the center of terrorism issues that discredit Islam.